Myeloid A20 is critical for alternative macrophage polarization and type-2 immune-mediated helminth resistance - Petta, Ioanna; Thorp, Marie; Ciers, Maarten; Blancke, Gillian; Boon, Louis; Meese, Tim; Van Nieuwerburgh, Filip; Wullaert, Andy; Grencis, Richard; Elewaut, Dirk; van Loo, Geert; Vereecke, Lars (Frontiers in Immunology, 2024)
Protective immunity against intestinal helminths requires induction of robust Type-2 immunity orchestrated by various cellular and soluble effectors which promote goblet cell hyperplasia, mucus production, epithelial proliferation, and smooth muscle contractions to expel worms and re-establish immune homeostasis. Conversely, defects in type-2 immunity result in ineffective helminth clearance, persistent infection, and inflammation. Macrophages are highly plastic cells that acquire an alternatively activated state during helminth infection, but they were previously shown to be dispensable for resistance to Trichuris muris infection. Nevertheless, we show that correct macrophage polarization is essential for helminth clearance, and we identify A20 as an essential myeloid factor for the induction of alternative macrophage polarization (M2-like) and subsequent type-2 immune responses upon infection with Trichuris muris. Myeloid cell-specific loss of A20 in mice (A20myel-KO) results in persistent Trichuris muris infection and intestinal inflammation. Myeloid A20 deficiency induces strong classical macrophage polarization which impedes anti-helminth type-2 immune activation, while instead promotes detrimental Th1/Th17 responses. Antibody-mediated neutralization of the type-1 cytokines IFNγ, IL18 and IL12 prevents myeloid-orchestrated Th1 polarization and re-establishes Type-2 mediated protective immunity against Trichuris muris in A20myel-KO mice. In contrast, the strong Th1 biased immunity in A20myel-KO mice offers protection against Salmonella typhimurium infection. We hereby identify A20 as a critical myeloid factor for correct macrophage polarization and appropriate adaptive mucosal immunity in response to helminth and enteric bacterial infection.